2020
DOI: 10.1016/j.isci.2020.101469
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Multiplexed In2O3 Nanoribbon Aptamer-Field-Effect Transistors for Biosensing

Abstract: Summary Flexible sensors are essential for advancing implantable and wearable bioelectronics toward monitoring chemical signals within and on the body. Developing biosensors for monitoring multiple neurotransmitters in real time represents a key in vivo application that will increase understanding of information encoded in brain neurochemical fluxes. Here, arrays of devices having multiple In 2 O 3 nanoribbon field-effect transisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 78 publications
4
87
0
Order By: Relevance
“…There were significant increases in FET responses 12 min after serotonin addition (see table S1 for statistics), demonstrating that the aptamer-FET neuroprobes detected diffusion-related changes in serotonin levels with respect to time. We previously found that the response times of our aptamer-FET sensors are on the order of seconds ( 21 , 23 ); the 12-min response time here is due to target diffusion over ~0.2 cm in the gelatin/aCSF matrix from the addition location to the recording site.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…There were significant increases in FET responses 12 min after serotonin addition (see table S1 for statistics), demonstrating that the aptamer-FET neuroprobes detected diffusion-related changes in serotonin levels with respect to time. We previously found that the response times of our aptamer-FET sensors are on the order of seconds ( 21 , 23 ); the 12-min response time here is due to target diffusion over ~0.2 cm in the gelatin/aCSF matrix from the addition location to the recording site.…”
Section: Resultsmentioning
confidence: 77%
“…To construct biosensors, thiol-terminated DNA aptamers were immobilized onto In 2 O 3 surfaces using (3-aminopropyl)triethoxysilane and 3-maleimidobenzoic acid N- hydroxysuccinimide ester for linking ( Fig. 3E ) ( 21 , 23 ). In vitro serotonin detection was performed in artificial cerebrospinal fluid (aCSF), which mimics the ionic strength and composition of the brain extracellular fluid ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…E-AB sensors were also developed for the detection of DA. Andrews’ group constructed flexible aptamer-field-effect-transistors for DA and 5-HT sensing with a 10 fM LOD [ 150 ]. However, most E-AB sensor work focuses on in vitro development and analysis only using serum or blood samples [ 151 , 152 , 153 ].…”
Section: Electrochemical Sensorsmentioning
confidence: 99%